Preliminary Screening for Antibacterial Activity of Endophytic Fungi isolated from Azadirachta indica and Mentha piperita against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa - Hussaini, Ibrahim Mohammed; Sadiya Ahmed , Halima; Ahmad , Hauwa’u; Sulaiman , Mamunu Abdulkadir; Usman , Aisha (Algerian Journal of Biosciences, 2022)
Endophytes have been identified as reservoirs of novel bioactive secondary metabolites that can serve as a potential candidate for the development of new antimicrobial drugs. The aim of the study was to screen for antibacterial activity of endophytic fungi isolated from Azadirachta indica and Mentha piperita. Endophytic fungi were isolated from healthy leaves of A. indica and M. piperita. The isolates were screened for their antibacterial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Antibacterial activity of ethyl acetate extracts of the isolates was also determined. A total 35 endophytic fungi were isolated out of which 11 showed antibacterial activity against at least two of the test bacterial isolates. Ethyl acetate extracts of these 11 endophytes had varying degree of antibacterial activity with zones of inhibition ranging from 10±10 mm to 26±0.5 mm. Result of this study revealed that endophytic fungi isolated leaves of A. indica and M. piperita produce bioactive compounds with antibacterial activity against the test bacterial isolates.